أثر استخدام الحكايات الرياضية في تدريس العمليات الحسابية لتنمية المفاهيم الرياضية واختزال القلق الرياضي لدى تلاميذ المرحلة الابتدائية - صاوي، يحيى زكريا Sawi, Yahia Zakaria (الجمعية المصرية لتربويات الرياضيات, 2019)
هدف البحث الحالي إلى دراسة أثر استخدام الحكايات الرياضية في تدريس العمليات الحسابية لتنمية المفاهيم الرياضية واختزال القلق الرياضي لدى تلاميذ المرحلة الابتدائية، وفي إطار تحقيق ذلك قام الباحث ببناء أدوات البحث والتي تمثلت في اختبار المفاهيم الرياضية ومقياس القلق الرياضي وخلصت نتائج البحث إلى: وجود فرق دال إحصائيا بين متوسطي درجات تلاميذ المجموعتين التجريبية والضابطة في التطبيق البعدي لاختبار المفاهيم الرياضية لصالح المجموعة التجريبية عند مستوي دلالة (0.01). وجود فرق دال إحصائيا بين متوسطي درجات تلاميذ المجموعتين التجريبية والضابطة في التطبيق البعدي لمقياس القلق الرياضي لصالح المجموعة التجريبية عند مستوي دلالة (0.05).
The current research aimed at investigating the effect of using mathematical tales in teaching mathematics to develop mathematical concepts and reducing the mathematical anxiety. In this context, the researcher designed the research instruments which represented in a mathematical concepts test and the mathematical anxiety scale. Results concluded that: There is a statistically significant difference between the mean scores of the students of experimental and control groups in the post-test for mathematical concepts for the experimental group at the level of 0.01. There is a statistically significant difference between the mean scores of the students of experimental and control groups in the post-test for mathematical anxiety scale for the experimental group at the level of 0.05.
Keywords: الحكايات الرياضية -- المفاهيم الرياضية -- القلق الرياضى -- تدريس الرياضيات -- المرحلة الابتدائية